Rehabilitative Effects of Virtual Reality Technology for Mild Cognitive Impairment: A Systematic Review With Meta-Analysis - Wu, Jinlong; Ma, Yudan; Ren, Zhanbing (Frontiers in Psychology, 2020)
Objective: To evaluate the impact of virtual reality (VR) technology on the cognitive functions (overall cognitive ability, executive function, short-term memory, and long-term memory) of people with mild cognitive impairment (MCI). Methods: All major databases, including Web of Science, PubMed, Scopus, Proquest, WanFang, and CNKI, were searched to identify all relevant studies published in English or Chinese since October 28th, 2019. Two researchers independently conducted document retrieval, study selection, data extraction, and methodological quality evaluation. Result: 15 randomized controlled trials were analyzed (N = 612 people with MCI), with the methodological quality evaluation score ranging from 5 to 7 points. A random effects model was selected to combine effect sizes. The result of the meta-analysis indicates that VR significantly enhanced MCI patients' overall cognitive ability (SMD = 0.869, 95% confidence interval [CI] = 0.330–1.407, P = 0.002, I2 = 86.822, n = 537) and executive function (SMD = 1.083, 95%, 95%CI = 00.134–2.031, P = 0.025, I2 = 93.748, n = 220). The meta-analysis indicated that after VR training, effects on short-term memory (SMD = 0.488, 95%CI = −0.108–1.084, P = 0.109, I2 = 62.354, n = 131) and long-term memory (SMD = 0.335, 95%CI = −1.194–0.863, P = 0.0.214, I2 = 58.868, n = 152) were not statistically significant. Conclusions: The present meta-analysis verifies the potential rehabilitative effects of VR technology for mild cognitive impairment.